Concordance between clinician, supervisor and observer ratings of therapeutic competence in CBT and treatment as usual: does clinician competence or supervisor session observation improve agreement?. Issue 3 (6th December 2019) - Caron, EB; Muggeo, Michela A.; Souer, Heather R.; Pella, Jeffrey E.; Ginsburg, Golda S.
Abstract: Background: Lowering the cost of assessing clinicians' competence could promote the scalability of evidence-based treatments such as cognitive behavioral therapy (CBT). Aims: This study examined the concordance between clinicians', supervisors' and independent observers' session-specific ratings of clinician competence in school-based CBT and treatment as usual (TAU). It also investigated the association between clinician competence and supervisory session observation and rater agreement. Method: Fifty-nine school-based clinicians (90% female, 73% Caucasian) were randomly assigned to implement TAU or modular CBT for youth anxiety. Clinicians rated their confidence after each therapy session ( n = 1898), and supervisors rated clinicians' competence after each supervision session ( n = 613). Independent observers rated clinicians' competence from audio recordings ( n = 395). Results: Patterns of rater discrepancies differed between the TAU and CBT groups. Correlations with independent raters were low across groups. Clinician competence and session observation were associated with higher agreement among TAU, but not CBT, supervisors and clinicians. Conclusions: These results support the gold standard practice of obtaining independent ratings of adherence and competence in implementation contexts. Further development of measures and/or rater training methods for clinicians and supervisors is needed.